The intake of flavonoids, stilbenes, and tyrosols, mainly consumed through red wine and virgin olive oil, is associated with lower carotid and femoral subclinical atherosclerosis and coronary calcium - Salazar, Henry Montero; de Deus Mendonça, Raquel; Laclaustra, Martín; Moreno-Franco, Belén; Åkesson, Agneta; Guallar-Castillón, Pilar; Donat-Vargas, Carolina (European journal of nutrition, 2022)
Purpose It is suggested that polyphenols back the cardiovascular protection offered by the Mediterranean diet. This study evaluates the association of specific types of dietary polyphenols with prevalent subclinical atherosclerosis in middle-aged subjects. Methods Ultrasonography and TC were performed on 2318 men from the Aragon Workers Health Study, recruited between 2011 and 2014, to assess the presence of plaques in carotid and femoral arteries and coronary calcium. Polyphenol intake was assessed using a validated semi-quantitative 136-item food frequency questionnaire. The Phenol Explorer database was used to derive polyphenol class intake. Logistic and linear regressions were used to estimate the cross-sectional association of polyphenols intake with femoral and carotid subclinical atherosclerosis and coronary calcium. Results A higher intake of flavonoids (third vs. first tertile) was associated with a lower risk of both carotid (OR 0.80: CI 95% 0.62–1.02; P trend 0.094) and femoral (0.62: 0.48–0.80, P trend < 0.001) subclinical atherosclerosis. A higher intake of stilbenes was associated with a lower risk of femoral subclinical atherosclerosis (0.62: 0.46–0.83; P trend 0.009) and positive coronary calcium (0.75: 0.55–1.03; P trend 0.131). A higher intake of tyrosols was also associated with a lower risk of positive coronary calcium (0.80: 0.62–1.03; P trend 0.111). The associations remained similar when adjusted for blood lipids and blood pressure. Conclusion Dietary flavonoids, stilbenes, and tyrosols, whose main sources are red wine and virgin olive oil, are associated with lower prevalence of subclinical atherosclerosis in middle-aged subjects.